The Basic Connotation, Cultivation Difficulties and Improvement Strategies of Digital Literacy for Physical Education Teachers in Primary and Secondary Schools - Xin, Songhe; Liang, Qiaomei (Journal of Research in Vocational Education, 2025)
Through methods such as literature review and logical analysis, combined with the current educational digitalization policies and practical background, the connotation of digital literacy for primary and secondary school physical education teachers is deconstructed, and the cultivation predicaments and improvement strategies are systematically sorted out. Research suggests that the digital literacy of physical education teachers in primary and secondary schools is a fundamental connotative system that encompasses four dimensions: digital awareness and attitude, digital knowledge and skills, digital application and innovation, and digital social responsibility. At present, its cultivation is confronted with core predicaments such as cognitive biases in concepts, superficial integration of technology and teaching, structural shortage of teachers’ digital capabilities, uneven resource support, and the absence of systematic training and evaluation mechanisms. To this end, it is necessary to build a multi-level and systematic improvement strategy system composed of teachers’ proactive actions, school environment support, top-level policy design and social collaborative efforts. Enhancing the digital literacy of physical education teachers in primary and secondary schools is a systematic project. It is hoped that through digital empowerment, the all-round development of students can be better promoted, and ultimately the fundamental mission of cultivating people through physical education can be achieved.